EFEKTIVITAS METODE BERMAIN SAMBIL BELAJAR PADA SISWA SEKOLAH DASAR - Wernita, Destri; Musdalifa, Dela; Aprillia, Fika; Rahim, Gafurur; Suriani, Ari; Safitri Syam, Salmaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The play-based learning method is an instructional approach that integrates play activities with the educational process. This study aims to examine the effectiveness of this method in improving the motivation and learning outcomes of elementary school students. The results of the study indicate that the play-based learning method is able to create an enjoyable learning environment, increase student engagement, and enhance conceptual understanding more effectively. Therefore, this method is highly relevant to be implemented in elementary school learning.